Poly(rC)-binding proteins as pleiotropic regulators in hematopoiesis and hematological malignancy - Zhao, Huijuan; Wei, Ziqing; Shen, Guomin; Chen, Yixiang; Hao, Xueqin; Li, Sanqiang; Wang, Rong (Frontiers in Oncology, 2022)
Poly(rC)-binding proteins (PCBPs), a defined subfamily of RNA binding proteins, are characterized by their high affinity and sequence-specific interaction with poly-cytosine (poly-C). The PCBP family comprises five members, including hnRNP K and PCBP1-4. These proteins share a relatively similar structure motif, with triple hnRNP K homology (KH) domains responsible for recognizing and combining C-rich regions of mRNA and single- and double-stranded DNA. Numerous studies have indicated that PCBPs play a prominent role in hematopoietic cell growth, differentiation, and tumorigenesis at multiple levels of regulation. Herein, we summarized the currently available literature regarding the structural and functional divergence of various PCBP family members. Furthermore, we focused on their roles in normal hematopoiesis, particularly in erythropoiesis. More importantly, we also discussed and highlighted their involvement in carcinogenesis, including leukemia and lymphoma, aiming to clarify the pleiotropic roles and molecular mechanisms in the hematopoietic compartment.